2020
DOI: 10.1029/2020jc016501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Limitation on Phytoplankton Physiology in the Western Arctic Ocean in Summer

Abstract: Phytoplankton in the Arctic Ocean are subject to nitrogen limitation in the summer, however, how severely the nitrogen stress affects phytoplankton physiology remains largely unknown. In the summers of 2015-2018, we examined the distribution of phytoplankton photophysiological properties across two contrasting regions of the Arctic Ocean with distinctly different levels of nitrogen availability in the upper water column. We quantified the extent of nitrogen stress using a highly sensitive fluorescence inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 85 publications
(125 reference statements)
3
25
0
Order By: Relevance
“…Previous studies of late-summer Arctic photophysiology have reported low background F v / F m values, as observed over most of our sampling transect. At the same time, these prior studies have also demonstrated increased F v / F m in response to nitrate (but not phosphate) enrichments [5], [50]. This result, coupled with the nutrient depletion observed at profiling stations along our cruise track (Table 2), suggest that the low F v / F m values we observed likely reflect nitrogen deficiency.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Previous studies of late-summer Arctic photophysiology have reported low background F v / F m values, as observed over most of our sampling transect. At the same time, these prior studies have also demonstrated increased F v / F m in response to nitrate (but not phosphate) enrichments [5], [50]. This result, coupled with the nutrient depletion observed at profiling stations along our cruise track (Table 2), suggest that the low F v / F m values we observed likely reflect nitrogen deficiency.…”
Section: Discussionsupporting
confidence: 84%
“…Nutrient enrichment experiments have demonstrated increasing τ Qa with nutrient deficiency and elevated actinic irradiance [30], [50]. Moreover, σ PSII can also change with nutrient availability, but the observed percent change in σ PSII following short-term nitrate enrichment is small compared with that of F v / F m [5], [50]. Baseline fluorescence, may also influence the terms used to define ETR k :ETR a .…”
Section: Decoupling Of Etra and Etrkmentioning
confidence: 99%
See 2 more Smart Citations
“…
The Arctic Ocean is undergoing rapid changes such as temperature rising, river runoff increasing, and sea ice decreasing, which profoundly impact the rapid-progressing biogeochemical cycle in the polar environments (Dai et al, 2019;Ko et al, 2020). The loss of sea ice increases photosynthesis and thus enhances the biological pump and primary production, while the increase of freshwater enhances the stratification in the ocean's upper layer, hindering the vertical mixing and material supply from the deep layer (Garnett et al, 2019;Morison et al, 2012;Nishino et al, 2011;Underwood et al, 2019).
…”
mentioning
confidence: 99%